Transatlantic Indians in the Early Modern Era - Holly, Nathaniel F. (History compass, 2016)
Many American Indians - as captives and of their own free will - crossed the Atlantic during the early modern period. Far too frequently, however, historians have been caught up in cataloging experiences - answering questions about what these indigenous travelers did when they were abroad. More penetrating questions about why transatlantic Indians embarked on these crossings or how these journeys affected their subsequent lives remain largely unasked. This essay will not only outline the chronologically long, but substantively limited historiography of transatlantic Indians, it will also argue for a more focused, contextually thorough, and ethnohistory-centric approach to the examination of these voyagers. Such a shift in methodology, moreover, will help the "Red Atlantic" congeal as a legitimate means of historical analysis.